2022
DOI: 10.3346/jkms.2022.37.e96
|View full text |Cite
|
Sign up to set email alerts
|

Does Post-Warming Extended Culture Duration Affect the Clinical and Obstetric Outcomes of Patients of Advanced Maternal Age? A Single-Center Study

Abstract: Background The single vitrified-warmed blastocyst transfer (SVBT) cycle has been increasingly utilized for assisted reproductive technology. Women of advanced maternal age (AMA) comprise a significant portion of patients who have undergone ‘freeze-all’ cycles. This study investigated the association between the post-warming extended culture duration and pregnancy outcomes in patients of AMA. Methods This retrospective cohort study analyzed the outcomes of 697 SVBT cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The discovery that fertilized embryos with artificial gaps in their zona pellucida appear to have high implantation rates and that divided embryos with an excellent prognosis for implantation have lessened the thickness of the zona led to the clinical introduction of assisted hatching. In addition, other studies reported that at the early stage of development some embryos showed dissimilarity in zona thickness and that zona thinning is an active development [26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that fertilized embryos with artificial gaps in their zona pellucida appear to have high implantation rates and that divided embryos with an excellent prognosis for implantation have lessened the thickness of the zona led to the clinical introduction of assisted hatching. In addition, other studies reported that at the early stage of development some embryos showed dissimilarity in zona thickness and that zona thinning is an active development [26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic change in speed is a potential indicator of developmental potential because the embryo changes prominently within a short period [ 42 , 43 ]. Most significantly, our previous study showed that morphological characteristics are the most important indicators of clinical outcomes and live birth [ 30 , 44 ]. Concordantly, in this study, we demonstrated that blastocyst diameter and re-expansion speed are closely related to embryo quality.…”
Section: Discussionmentioning
confidence: 99%
“…The vitrified-warmed blastocyst survival and grading assessments were performed as described in our previous study [ 10 , 30 ]. In brief, embryologists assessed the degree of post-warming blastocyst survival by identifying viable cells (clear margin and homogeneous content) in comparison to dead cells (dark and granular) and defined fully surviving embryos when >50% of intact cells were observed.…”
Section: Methodsmentioning
confidence: 99%